Effect of landscape density in a residential area on thermal performance in a tropical climate - Kamarulzaman, N. (EDP Sciences, 2016)
It is a well-documented that the urban air temperature is gradually growing in all cities due to the rapid development of buildings, roads and other infrastructure, human activities and also decreasing in vegetated areas. In a tropical climate, outdoor environment is clearly warmer than indoor environment due to higher air temperatures, particularly in dry seasons. Since the indoor environment is influenced by its surroundings, this situation indirectly contributes to the discomfort indoor environment in the building. Thus, it generates to the dependence on mechanical ventilation and increase the energy consumption in buildings. Many research studies have proof that plants not only beauty a city, but also improve the urban environmental condition by reducing the transferring of heat flux on buildings and increasing the reflection of radiation and shading. Therefore strategically placed vegetation around a building could decrease the energy consumption in buildings by reducing the adverse impact of some climate elements. Overall, this paper focuses on the results of a preliminary pilot study of two Semi-Detached houses with different landscape density in Seri Iskandar, Perak. Three climatic parameters, building configuration, and landscape design measured and analyze in this paper. Â© 2016 The Authors.